Exploring communication through qualitative research - Daba-Buzoianu, Corina, 1983-; Bîră, Monica; Duduciuc, Alina; Tudorie, George (Cambridge Scholars Publishing, 2017)
This volume offers an insight into contemporary communication studies, as seen through the lens of qualitative research. It presents existing studies on qualitative research, current research programs, and trends for future expansion of this methodological approach. It also offers a series of practical examples of applying methods and techniques of qualitative research, to teach readers about the social world and to answer pressing problems related to applied communication. In terms of research, the studies within the book use focus-group interviews, in-depth interviews, qualitative content ana.